Des néo-canadiens intégrés : les portugais de Hull. - Martin, Rozenn Marguerite. (University of Ottawa (Canada), 1999)
In this thesis, the complexity of immigrant's integration into Canadian society through the life experiences and perspectives of the members of the well established Portuguese community of Hull, is examined. The focus of this paper is on the impact of ethnic environments, whether they serve a residential, social or cultural purpose on Portuguese integration processes. Integration is difficult to measure since it occurs in various ways at different rate depending on individual immigrants and the successive generations. Nevertheless, the interviews with a group of Portuguese immigrants representative of their community, have revealed that once settled in Canada, their main concern is to achieve a level of "complete" and "absolute" integration into Canadian society. By analysing the role of ethnic neighbourhood, the involvement with ethnic institutions, the need to preserve the Portuguese culture and to maintain strong family ties, and by taking into account the Portugueses's feelings, an attempt was made to ascertain if Portuguese migrants were integrated into Canadian society. In order to reflect the diversity of behaviour and opinions among the Portuguese immigrants, a typology was subsequently established.
Keywords: Geography.